Electromagnetic Transient Modeling of Asynchronous Machine in Modelica, Accuracy, and Performance Assessment - Alireza Masoom; Jean Mahseredjian (IEEE Access)
Classical EMT-type simulators are mostly programmed in procedural languages, e.g. Fortran or C. In these languages, the focus is mainly on the solution methods. Modern languages, such as Modelica, are declarative and primarily focused on modeling and simulation. Modelica offers a much higher abstraction level, which makes the codes more concise and understandable. This paper contributes to the electromagnetic transient modeling and simulation of asynchronous machines in Modelica. In this paper, the modeling of a three-phase squirrel cage (single and double cage) and wound-rotor induction machine in three different reference frames is described and implemented. The accuracy and performance of Modelica models are compared and validated with the classical modeling approach used in the reference software EMTP. It is demonstrated that Modelica-based models with variable-step solvers offer fast and accurate results for time-domain simulations of motor sequential startup cases.